From canonical criticism to ecumenical exegesis? : a study in biblical hermeneutics - Smit, Peter-Ben, 1979- (Studies in Reformed Theology, 2015)
This study explores and compares the role of the canon in the work of Brevard S. Childs, James A. Sanders, Peter Stuhlmacher, Joseph Ratzinger/Benedict XVI, and the Amsterdam School of exegesis, thus offering a broad overview of approaches and perspectives within the spectrum covered by canonical criticism. In doing so, both the theory of canonical criticism offered by each of the five is analysed and a sample of an actual exegesis is discussed. Observing that the interplay between text, reader, and community of interpretation is key to all of these approaches, the study proceeds to create a dialogue between canonical criticism and ecumenical hermeneutics, which leads to a proposal for an approach to exegesis that integrates elements of canonical hermeneutics, ecumenical hermeneutics, and intercultural perspectives.